Coordinated air-ground scheduling for UAV-assisted cell-free massive MIMO - Danhao DENG; Chaowei WANG; Fan JIANG; Weidong WANG (Dianxin kexue)
Cell-free massive multiple-input multiple-output (MIMO) technology uses a large number of access points (AP) to provide efficient communication services for terrestrial users.However, massive APs and users increase the demand for channel state information detection, especially for users with high moving speeds.In order to reduce the consumption of pilot resources, a dual system architecture that integrates unmanned aerial vehicle-assisted (UAV-assisted) communications and cell-free massive MIMO communications was proposed.The architecture was able to predict the movement trajectories of high-speed users and use UAVs to provide them with reliable communications.A UAV trajectory design and user scheduling scheme based on deep reinforcement learning (DRL) was further proposed, which maximized the system sum rate under the premise of satisfying various constraints.Simulation results demonstrate that the proposed scheme is able to predict user trajectories and improve system sum rate compared with existing schemes.